Draft Genome Assembly of the Aral Barbel Luciobarbus brachycephalus Using PacBio Sequencing. (13th July 2021) - Geng, Longwu; Zou, Ming; Jiang, Haifeng; Meng, Minghui; Xu, Wei
Abstract: The endangered Aral barbel Luciobarbus brachycephalus is endemic to the water systems of the Caspian Sea and Aral Sea. Given the scarcity of genetic data for the species, we present a draft assembly based on PacBio long-read sequencing technology. Approximate 299.4 Gb of long reads representing 166× of the estimated genome size were generated, and the final assembly was composed of 653 contigs totaling approximately 1, 698.3 Mb, with a contig N50 length of 4.5 Mb. A total of 807.6 Mb represented approximately 47.6% of the assembly and were identified as repeats. Fifty-four thousand and six hundred possible protein genes were predicted, among which 50, 727, representing approximately 92.9%, could be annotated by at least one database. Evolutionary analysis showed that L . brachycephalus and Labeo rohita diverged by approximately 42.6 Ma, and the obvious expansion of gene families residing in the L . brachycephalus genome may be attributed to the specific whole-genome duplication of the species. The first genome assembly of L . brachycephalus can not only provide a foundation for genetic conservation and molecular breeding of this species but also contribute to comparative analyses of genome biology and evolution within Cyprinidae.